Aquaporin-4 antibodies (NMO-IgG) as a serological marker of neuromyelitis optica: a critical review of the literature - Jarius, Sven; Wildemann, Brigitte (Brain pathology, 2013)
Antibodies to aquaporin-4 (called NMO-IgG or AQP4-Ab) constitute a sensitive and highly specific serum marker of neuromyelitis optica (NMO) that can facilitate the differential diagnosis of NMO and classic multiple sclerosis. NMO-IgG/AQP4-Ab seropositive status has also important prognostic and therapeutic implications in patients with isolated longitudinally extensive myelitis (LETM) or optic neuritis (ON). In this article, we comprehensively review and critically appraise the existing literature on NMO-IgG/AQP4-Ab testing. All available immunoassays—including tissue-based (IHC), cell-based (ICC, FACS) and protein-based (RIPA, FIPA, ELISA, Western blotting) assays—and their differential advantages and disadvantages are discussed. Estimates for sensitivity, specificity, and positive and negative likelihood ratios are calculated for all published studies and accuracies of the various immunoassay techniques compared. Subgroup analyses are provided for NMO, LETM and ON, for relapsing vs. monophasic disease, and for various control groups (eg, MS vs. other controls). Numerous aspects of NMO-IgG/AQP4-Ab testing relevant for clinicians (eg, impact of antibody titers and longitudinal testing, indications for repeat testing, relevance of CSF testing and subclass analysis, NMO-IgG/AQP4-Ab in patients with rheumatic diseases) as well as technical aspects (eg, AQP4-M1 vs. AQP4-M23-based assays, intact AQP4 vs. peptide substrates, effect of storage conditions and freeze/thaw cycles) and pitfalls are discussed. Finally, recommendations for the clinical application of NMO-IgG/AQP4-Ab serology are given.
Gesehen am 25.03.2021
Mini-symposium: Neuromyelitis Optica (NMO), Part 1